The Use of Activated and Non-Activated Tar Sands as Adsorbents for Copper Ion Removal - Lua'y Zeatoun; Shadi Yousef (Adsorption Science & Technology)
Jordanian tar sands were used as an adsorbent for the removal of copper ions from aqueous solutions. Experimental results showed that the adsorption of Cu 2+ ions onto tar sands was pH- and temperature-dependent. Copper ion uptake increased with increasing pH, temperature and initial adsorbate concentration, but decreased with adsorbent concentration. An increase of ca. 40% in the uptake was noted when the tar sands were activated physically with CO 2 . The presence of NaCl salt in the adsorption process influenced the uptake of Cu 2+ ions by the adsorbent studied. The adsorption process was very fast with equilibrium being achieved in about 2 min. The experimental data were well represented by both the Langmuir and Freundlich isotherm models.